Experimental studies on heat transfer and friction factor characteristics of Al2O3/water nanofluid under laminar flow with spiralled rod inserts. (1st January 2012) - Suresh, S.; Chandrasekar, M.; Selvakumar, P.; Page, Tom
An experimental investigation on the convective heat transfer and friction factor characteristics in the plain and spiralled rod inserts (pitch = 15 mm, 30 mm) in a plain tube under laminar flow with constant heat flux is carried out with Al2 O3 -water nanofluids. We study the effect of the inclusion of nanoparticles on heat transfer enhancement, thermal conductivity, viscosity, and pressure loss in the laminar flow region. For this, we synthesised Al2 O3 nanoparticles by using microwave assisted chemical precipitation method and we measured size of nanoparticles by using XRD. The average size of particle is 40.3 nm, and then the nanoparticles dispersed in distilled water to form stable suspension containing 0.3%, 0.4%, 0.5% volume concentration of nanoparticles. The experimental results of Nusselt number for 0.5% nanofluid with spiralled rod inserts under laminar flow showed a maximum of 24% higher than the plain tube and the isothermal pressure drop of nanofluids with spiralled rod inserts were about 5% to 15% higher than the plain tube.